Tinjauan Efek Neuroprotektif Fukoidan terhadap Model Tikus Stroke Iskemik - Fidha Rahmayani; Muhammad Irsan Saleh; Nur Arfian; Zen Hafy (Universitas Malahayati, 2026)
ABSTRACT Ischemic stroke is the most common type of stroke and remains the leading cause of disability and the second leading cause of death worldwide. The definitive therapies recommended by the Food and Drug Administration (FDA) for acute ischemic stroke are tissue plasminogen activator (t-PA) and mechanical thrombectomy, which have a very narrow therapeutic window. Therefore, additional supportive therapy is needed to achieve more optimal functional improvement and reduce post-stroke morbidity. Fucoidan, as one of the active compounds in brown algae, plays a role as an antioxidant, anti-inflammatory, anti-adhesive, and anti-apoptotic agent in management of ischemic stroke. to study the pharmacological properties of the active compound fucoidan derived from brown algae and analyze the neuroprotective role of fucoidan in ischemic stroke through a systematic review of various studies that have been conducted. The literature review method used the narrative review technique. Literature searches were conducted in the PubMed Central, Google Scholar, EMBASE/Elsevier, and Wiley Library databases for articles published between 2015 and 2025. The keywords used were a combination of disease terms, exposure, and molecular pathways combined with Boolean operators (AND/OR) and adjusted for each database. The synthesis results show that fucoidan belongs to the sulfated polysaccharide group, which is rich in α L-fucose and sulfate groups that determine various biological activities of fucoidan. The molecular mechanism of fucoidan in complementary therapy for ischemic stroke has been studied in various in vitro experimental, plays a role as an anti-inflammatory, antioxidant, antiapoptotic, mitochondrial damage protection, blood-brain barrier repair, and neurogenesis enhancement. Fukoidan has neuroprotective effects against ischemic stroke through anti-inflammatory, antioxidant, anti-apoptotic, mitochondrial damage protection, blood-brain barrier repair, and neurogenesis enhancement mechanisms. However, further research is needed on the molecular pathways involved to aid in the development of comprehensive management of ischemic stroke. Keywords: Cerebral Ischemia, Fucoidan, Molecular Pathways. ABSTRAK Stroke iskemik adalah klasifikasi stroke dengan jumlah kasus terbanyak dan masih menjadi penyebab utama kecacatan dan penyumbang angka kematian tertinggi kedua di seluruh dunia. Terapi definitif yang direkomendasikan oleh Food and Drug Administration (FDA) untuk stroke iskemik akut adalah tissue plasminogen activator (t-PA) dan trombektomi mekanis, yang memiliki jendela terapeutik yang sangat sempit. Sehingga diperlukan terapi tambahan yang bersifat suportif untuk memperoleh perbaikan fungsional yang lebih optimal dan mengurangi morbiditas paska stroke. Fukoidan sebagai salah satu senyawa aktif alga cokelat memiliki peranan sebagai antioksidan, antiinflamasi serta anti adesif serta antiapoptosis dalam tatalaksana stroke iskemik. untuk mempelajari sifat farmakologi senyawa aktif fukoidan yang bersumber dari alga cokelat serta menganalisis peran neuroprotektif fukoidan pada stroke iskemik melalui sistematik review dari berbagai penelitian yang sudah dilakukan. metode literatur review menggunakan teknik narrative review. Pencarian literatur dilakukan pada basis data PubMed Central, Google Scholar, EMBASE/Elsevier,dan Wiley Library pada artikel yang terbit dalam periode 2015-2025. Kata kunci yang digunakan adalah kombinasi istilah penyakit, paparan, dan jalur molekular yang digabungkan dengan operator Boolean (AND/OR) dan disesuaikan dengan masing-masing database. Hasil sintesis menunjukan bahwa fukoidan termasuk dalam golongan polisakarida tersulfatisasi yang kaya akan α L-fukosa dan gugus sulfat yang berperan sebagai penentu berbagai aktivitas biologis fukoidan. Mekanisme molekular fukoidan dalam terapi komplementer stroke iskemik telah dibuktikan dalam berbagai penelitian in vitro yaitu berperan sebagai anti inflamasi, antioksidan, antiapotosis, perlindungan kerusakan mitokondria, perbaikan sawar darah otak serta meningkatkan neurogenenis. Fukoidan memiliki efek neuroprotektif terhadap stroke iskemik melalui mekanisme anti inflamasi, antioksidan, antiapotosis, perlindungan kerusakan mitokondria, perbaikan sawar darah otak serta meningkatkan neurogenenis. Namun, dibutuhkan penelitian lanjutan terkait jalur molekular yang terlibat sehingga dapat membantu pengembangan tatalakasana komprehensif pada stroke iskemik. Kata Kunci: Stroke Iskemik, Fukoidan, Jalur Molekular.